Akulturasi Agama dan Budaya dalam Wisata Religi: Studi Kasus Pesarean Gunung Kawi Malang - Novi Amalia (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This study deeply analyzes the complex process of religious and cultural acculturation in Pesarean Gunung Kawi, Malang. Using a descriptive qualitative approach, this study reveals how the unique blend of Islam, Javanese, and Chinese has shaped distinctive religious traditions, architecture, and social practices. In addition, this study also examines how the acculturation process has shaped the collective identity of the local community and its impact on the social, cultural, and economic dynamics in the area. The findings of this study indicate that Pesarean Gunung Kawi is a real example of how religion and culture can enrich each other and form a harmonious and pluralistic social order.